Analysis of Local Wisdom Values in The Ghofilinan Tradition in Katimoho Village, Gresik Regency - Fajar Bangun Wiradani (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
The research departed from the phenomenon of the elimination of elements of local culture in society. One of the causes was the current modernization and globalization of all aspects of life, including traditions and culture. The formation of noble values that were able to pattern the behavior of the Indonesian people was due to the decisive role of customs, which became a culture in people's lives. Although the customs and culture of each region were different, in general, they had the same essential values. Traditional and cultural philosophies that have developed in various parts of the Indonesian nation, on average, instill good and positive moral attitudes and behaviors. This research objective was to find the local wisdom values and the Ghofilinan tradition in the Katimoho Village community. This research was a qualitative method. Data were collected from primary and secondary sources. Primary sources were carried out by direct observation (natural observation). For in-depth review, interviews were carried out. Secondary data was obtained through literature study and village documentation. The research results concluded that the Ghofilin tradition had religious, social, historical, and economic values that coexisted with Islamic values. Islam is a religion with a set of values that have influenced the cultural patterns and traditions of the Katimoho Village community. The meeting of Islamic values with the local wisdom values in the Dzikrul Ghofilin tradition was a process of cultural acculturation. It made the socio-cultural aspects of the local community not necessarily eroded by Islamic teachings.